Digital Transformation In Human Resource Management: Strategy And Implementation - Yulianah Yulianah (Jurnal Ekonomi, 2024)
Digital transformation in human resource management (HR) has become the main focus for organizations around the world in facing the industrial era 4.0. This research aims to explore the strategy and implementation of digital transformation in HR management, as well as its impact on operational efficiency and employee satisfaction. Using a qualitative approach, data analysis of related literature. The results of this research show that the strategy and implementation of digital transformation in human resource management (HR) has a significant positive impact on the efficiency and effectiveness of various HR processes. The use of technology such as HR information systems (HRIS), e-learning platforms, and data-driven analytical tools speed up administrative processes, increase the accuracy of performance evaluations, and enable more flexible training management. In addition, the application of artificial intelligence (AI) and machine learning in recruitment and performance management increases speed and objectivity in the process. Thus, digital transformation not only improves operational processes but also improves employee experience and satisfaction, contributing to organizational success and competitiveness .. This research concludes that successful digital transformation in HR management requires careful strategic planning, support from top management, and active involvement from all stakeholders.